Descriptive Analysis on Flouting and Hedging of Conversational Maxims in the “Post Grad” Movie - Nastiti Rokhmania (Register Journal, 2012)
This research is focused on analyzing flouting and hedging of conversational maxim of utterances used by the main characters in “Post Grad” movie. Conversational maxims are the rules of cooperative principle categorized into four categories; Maxim of Quality, Maxim of Quantity, Maxim of Relevance, and Maxim of Manner. If these maxims are used in  conversations, the conversations can go smoothly. However, people often break the maxims overtly (flouting maxim) and sometimes break the maxims secretly (hedging maxims) when they make a conversation. This research is conducted using descriptive qualitative method based on the theory known as Grice’s Maxims. The data are in form of utterances used by the characters in “Post Grad” movie. The data analysis reveals some finding covering the formulated research question. The maxims are flouted when the speaker breaks some conversational maxims when using the utterances in the form of rhetorical strategies, such as tautology, metaphor, hyperbole, irony, and rhetorical question. On the other hand, conversational maxims are also hedged when the information is not totally accurate or unclearly stated but seems informative, well-founded, and relevant.Keywords: Descriptive analysis ; flouting maxims; hedging maxims;  Post Grad movie.